Impact of Tidal Flooding on Sanitation Damage and Disease Patterns in Coastal Areas - Lieza Corsita; Bayu Samudra (Knowledge and Environmental Science for Living and Global Health, 2026)
Tidal flooding (rob) has become a persistent environmental hazard in Indonesia’s coastal regions, particularly in Pekalongan City, Central Java, leading to significant degradation of basic sanitation infrastructure and increased health risks. This study aims to analyze the impact of tidal flooding on sanitation facility damage and the shifting patterns of disease among coastal communities. A quantitative cross-sectional design was employed involving 120 households in flood-prone areas of North Pekalongan. Data were collected through structured interviews, direct observation, and secondary health records from local health centers. Variables included sanitation condition, water quality, and incidence of waterborne and environmentally related diseases. Statistical analysis using chi-square and logistic regression revealed a significant relationship between sanitation damage and increased incidence of diarrhea, skin diseases, and acute respiratory infections (p < 0.05). Households with damaged sanitation facilities had a 2.8 times higher risk of experiencing diarrhea (OR = 2.8; 95% CI: 1.4–5.6). Approximately 65% of sanitation facilities were found to be damaged or non-functional during flooding periods, leading to contamination of clean water sources. These findings highlight the urgent need for climate-resilient sanitation systems, including flood-adaptive septic tank designs and improved wastewater management in coastal settlements. The study concludes that tidal flooding significantly contributes to sanitation degradation and alters disease patterns in coastal populations.